Nano-sized Mn oxides as true catalysts for alcohol oxidation by a mononuclear manganese(ii) complex1. Issue 34 (14th September 2015) - Najafpour, Mohammad Mahdi; Ebrahimi, Foad; Amini, Mojtaba; Rahimi, Mohammad; El-Sawy, Abdelhamid; Suib, Steven L.
<x xml:space="preserve">Abstract</x> We propose that nano-sized Mn oxides are true catalysts for the oxidation of some alcohols to aldehydes in the presence of a mononuclear manganese(ii) complex, and Oxone as an oxidant.